The claims of kinfolk : African American property and community in the nineteenth-century South - Penningroth, Dylan C. (John Hope Franklin series in African American history and culture., 2003)
In The Claims of Kinfolk, Dylan Penningroth uncovers an extensive informal economy of property ownership among slaves and sheds new light on African American family and community life from the heyday of plantation slavery to the ""freedom generation"" of the 1870s. By focusing on relationships among blacks, as well as on the more familiar struggles between the races, Penningroth exposes a dynamic process of community and family definition. He also includes a comparative analysis of slavery and slave property ownership along the Gold Coast in West Africa, revealing significant difference.